2022
DOI: 10.1002/adsc.202200957
|View full text |Cite
|
Sign up to set email alerts
|

From Peripheral Stereogenic Center to Axial Chirality: Synthesis of 3‐Arylthiophene Atropisomers

Abstract: A practical synthesis of axially chiral biaryls via chirality transfer from peripheral stereogenic carbon centers is reported. In contrast to the traditional aromatization process of a non-aromatic structure with ipso stereogenic centers, this method is based on a Pd-catalyzed carbon-carbon bond cleavage/ring-opening reaction of optically active 8H-indenothiophen-8-ols with an achiral ligand, enabling synthesis of highly functionalized 3-arylthiophene atropisomers in high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In 2022, we observed that optically active 8 H -indeno [1,2-c]thiophen-8-ols would undergo a stereoselective ring-opening reaction with an achiral palladium complex, resulting in the formation of axially chiral biaryls ( Scheme 1 b) [ 34 , 35 ]. This chirality relay is based on the fact that one of the aryl rings would approach the Pd atom, ultimately resulting in the construction of axial chirality.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, we observed that optically active 8 H -indeno [1,2-c]thiophen-8-ols would undergo a stereoselective ring-opening reaction with an achiral palladium complex, resulting in the formation of axially chiral biaryls ( Scheme 1 b) [ 34 , 35 ]. This chirality relay is based on the fact that one of the aryl rings would approach the Pd atom, ultimately resulting in the construction of axial chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, endeavors for the preparation of enantiopure VI were unsuccessful: the Pd-catalyzed carbonylation/cyclization of enantiopure IV at 120 °C gave a 45% yield of intermediate V but with a significantly eroded enantiomeric excess (ee) value. Inspired by the aforementioned results and our previous work, we present here a palladium-catalyzed kinetic resolution of helicenols. This method allows for the concurrent generation of chiral helicenols and sterically hindered biaryl atropisomers (Scheme c).…”
mentioning
confidence: 99%
“…Recently, we have developed a Pd-catalyzed kinetic resolution reaction of 8 H -indeno­[1,2- c ]­thiophen-8-ols via stereoselective ring opening . Notably, in addition, the optically active 8 H -indeno­[1,2- c ]­thiophen-8-ols obtained at the kinetic resolution mentioned above would undergo Pd-catalyzed ring-opening reaction with nearly full point to axial chirality transfer in the presence of an achiral phosphine ligand (Scheme c) . Taking advantage of this chirality transfer process, we are keen to develop a Pd-catalyzed domino cyclization reaction/ring-opening reaction to construct atropisomers with multiple chiral axes, such as vinyl–aryl and aryl–aryl axes (Scheme d).…”
mentioning
confidence: 99%